“Gestión Y Desarrollo Turístico en la Comunidad de Tondolique, Parroquia Quisapincha, Provincia de Tungurahua” - Pullutasig Tamaquiza, Ana Gabriela (2019)
In this research work "Tourism Management and Development in the Tondolique Community, Parish Quisapincha, Province Tungurahua ", the current situation of the community Tondolique, was analyzed and situation, both general and specific objectives, the theoretical bases related to the variables are analyzed,in other words,the background of other researches that serve as a basis to deepen the study. This investigation is carried out with the support of the inhabitants of the community Tondolique, the GADPR Quisapincha and a group of teachers of UNACH of tourism and hotel management school. The research work has a methodology, that is, the path that must be followed to achieve the objectives and their respective solutions. Subsequently, the tabulation is carried out to make the tables and graphs that help the interpretation, analysis and the conclusions of the results obtained. Therefore, it is proposed to implement management strategies that include planning, organization, leadership, control, to promote tourism development in the Tondolique community contributing to the solution of problems, promoting tourism in a more definite and more precise way, For this reason, it is necessary that the people involved in the tourism field take into consideration each of the strategies mentioned in the proposal.